Implementasi Proyek Penguatan Profil Pelajar Pancasila pada Kurikulum Merdeka di Mas Tahfizhil Qur’an Islamic Centre - Febri Nanda Monalisa (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The research that has been carried out is entitled "Implementation of the Project to Strengthen the Profile of Pancasila Students at MAS Tahfizhil Qur'an Islamic Center" based on the fact that almost all schools have implemented the project to strengthen the profile of Pancasila students, but there is still confusion in its implementation. Some teachers consider this project to be related to extracurricular learning content, and have difficulty understanding assessment for project learning. This research methodology uses a qualitative approach, with information sources being the head of the madrasa, the deputy head of the madrasa for curriculum, and teachers at the MAS Tahfizhil Quran Islamic Center. The techniques used in collecting data are observation, interviews and documentation. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The results of the research revealed that (1) Planning for P5 RA at MAS Tahfizhil Qur'an Islamic Center started from forming a facilitator team consisting of class 10 homeroom teachers and subject teachers, identifying the level of readiness of the educational unit which in this case was still in the developing stage, designing dimensions , themes, and time allocation P5 RA has two themes in two semesters, namely the first theme will be implemented on November 4 2023, while the second theme will be on May 2, 3 and 4 2024, compiling project modules, and designing project results reporting strategies using documentation from project implementation, (2) Implementation of P5 RA at MAS Tahfizhil Qur'an Islamic Center is carried out in the stages of introduction, action and reflection, in these stages there are still shortcomings because MAS Tahfizhil Qur'an Islamic Center has only adopted the independent curriculum in the academic year 202/32024, (3) Evaluation is carried out by documenting and reporting the results of the student profile strengthening project as well as evaluation of the Pancasila student profile strengthening project.